ESTIMASI KEMAMPUAN LITERASI MATEMATIKA SISWA SMP DENGAN MODEL PENSKORAN PARCIAL CREDIT MODEL (PCM) PADA KONTEN KUANTITAS - Fitriana, Dyah Ayu (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2022)
This research aims to measure students' mathematical literacy abilities at SMP N 1 Tempel. This research uses a quantitative survey design method. The population of all 7th grade students at SMP N 1 Tempel by random sampling consisted of 63 students with high, medium and low abilities. Data collection was carried out with a test consisting of 10 questions about mathematical literacy in quantity content. The scoring model used in this research is the partial credit model (PCM) with 3 categories, namely 0,1,2. The data analysis used includes construct validity, content validity, level of difficulty, instrument reliability, and estimation of students' literacy abilities. Data analysis using the help of quest software and Ms. Excel 2010. The results of the research show that the mathematical literacy abilities of students at SMP N 1 Tempel in quantity content are in the medium category, namely in the range -1.77 to +0.33.